2015
DOI: 10.5194/hess-19-3217-2015
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change on temperature, precipitation and hydrology in Finland – studies using bias corrected Regional Climate Model data

Abstract: Abstract. Assessment of climate change impacts on climate and hydrology on catchment scale requires reliable information about the average values and climate fluctuations of the past, present and future. Regional climate models (RCMs) used in impact studies often produce biased time series of meteorological variables. In this study bias correction (BC) of RCM temperature and precipitation for Finland is carried out using different versions of the distribution based scaling (DBS) method. The DBS-adjusted RCM da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 33 publications
1
62
0
Order By: Relevance
“…To further explore the scale-driven uncertainty of the IDF curves, future IDF curves from the four stations were constructed for five time scales and 11 RCM ensemble members using a distribution-based scaling (DBS) [30,31] approach to remove the bias of the RCM. A statistical downscaling method that combined nonparametric prediction models and the method of fragments framework (NPRED-MoF) [15] was used to disaggregate future daily rainfall to hourly or sub-hourly scales.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To further explore the scale-driven uncertainty of the IDF curves, future IDF curves from the four stations were constructed for five time scales and 11 RCM ensemble members using a distribution-based scaling (DBS) [30,31] approach to remove the bias of the RCM. A statistical downscaling method that combined nonparametric prediction models and the method of fragments framework (NPRED-MoF) [15] was used to disaggregate future daily rainfall to hourly or sub-hourly scales.…”
Section: Methodsmentioning
confidence: 99%
“…The rainfall intensities for different return periods (2, 5, 10, 25, 50, and 100 years) were then calculated, and the five types of IDF curves based on the rainfall intensity from six return periods and 24 durations could be plotted. In this study, the bias-correction procedure for the RCM precipitation and temperature predominantly depended on the DBS approach described by Yang et al [30] and Olsson et al [31]. This method adjusts the distribution of RCM data to make it consistent with the distributions of the observation data based on cumulative distribution functions (CDFs) and then determines the new RCM data distribution parameters estimated by the maximum likelihood.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may significantly change the original modeled long-term trend or other higher moments of the climate variable statistics that eventually change the long-term signal of the climate variable. In their work on distribution-based scaling (DBS) bias correction, Olsson et al (2015) showed that their methodology might alter the long-term temperature trends, attributing the phenomenon in the severity of the biases in the mean or the standard deviation between the uncorrected temperatures and the observations. Maraun (2016) discusses whether the change in the trend is a desired feature of bias correction, concluding that it is case-specific and depends on the skillfulness of the climate model to simulate the correct long-term signal.…”
Section: Introductionmentioning
confidence: 99%